2006
DOI: 10.1007/s11136-005-4365-7
|View full text |Cite
|
Sign up to set email alerts
|

Validating, Improving Reliability, and Estimating Correlation of the Four Subscales in the WHOQOL-BREF using Multidimensional Rasch Analysis

Abstract: Objective: This study examined the construct validity, and improved the test reliability and the estimation accuracy for the correlation between domains of the WHOQOL-BREF using multidimensional Rasch analysis. Method: A total of 13,083 adults were administered the 28-item WHOQOL-BREF Taiwan version, which consists of 4 subscales (domains). The multidimensional form of the partial credit model was used to examine the fit of the 4 subscales. For comparison, each subscale individually was also fitted to the unid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
2
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 30 publications
4
57
2
4
Order By: Relevance
“…Em relação à qualidade de vida, os diversos trabalhos publicados até aos dias de hoje referiram-se às propriedades psicométricas do WHOQOL (13,(17)(18)(19)(20)(21)(22) , bem como à utilização do mesmo em amostras de pacientes psiquiátricos ou em estado de internação (23)(24)(25)(26)(27) e na população idosa (28)(29)(30) . O Brasil é um país onde parcela significativa da população (14,5%) é portadora de algum tipo de deficiência (31) .…”
Section: Análise Do íNdice Da Qualidade De Vida Por Dimensõesunclassified
“…Em relação à qualidade de vida, os diversos trabalhos publicados até aos dias de hoje referiram-se às propriedades psicométricas do WHOQOL (13,(17)(18)(19)(20)(21)(22) , bem como à utilização do mesmo em amostras de pacientes psiquiátricos ou em estado de internação (23)(24)(25)(26)(27) e na população idosa (28)(29)(30) . O Brasil é um país onde parcela significativa da população (14,5%) é portadora de algum tipo de deficiência (31) .…”
Section: Análise Do íNdice Da Qualidade De Vida Por Dimensõesunclassified
“…The Mandarin Chinese version of the WHOQOL-BREF currently exists in Taiwan [7][8][9]. However, this tool cannot be applied to more than half of elderly Taiwanese aged over 65 years old [10], who speak only the Taiwanese dialect [11].…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by previous researchers (Wang, Yao, Tsai, Wang, & Hsieh, 2006), a difference equal to or larger than 0.5 logits was regarded as evidence of substantial DIF. The results showed indicated that no substantial DIF was found.…”
Section: Resultsmentioning
confidence: 87%
“…The multidimensional approach could calibrate all subscale at the same time, and increase the measurement precision by taking into account the correlations between subscales (Wang, Yao, Tsai, Wang, & Hsieh, 2006). It can be observed in Table 4 that the correlations among subscales ranged from .52 to .73, showing medium to high correlation levels.…”
Section: Resultsmentioning
confidence: 99%